1999
DOI: 10.2355/isijinternational.39.697
|View full text |Cite
|
Sign up to set email alerts
|

Injection of Flux into the Blast Furnace via Tuyeres for Optimising Slag Formation.

Abstract: E-mai l: J itang. Ma@km, Iuth,se Based on discussion of the slag formation problems occurred during a commercial sca[e blast furnace test of I OO'/• high Fe-content self-fluxed pellets, a proposal of replacing the charge of flux from the top by injection via tuyeres has been presented. It will optimise the slag formation process and provide a great potential of further increase productivity with smooth operation due to: I ) decrease bosh slag volume significantly;2) obtain even and proper basicities of prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 1 publication
1
14
0
Order By: Relevance
“…To decrease the variations in slag basicity and the slag amount in the cohesive zone, Ma 1) has proposed injection of fluxes through the tuyeres, instead of charging them from the top, to improve slag formation in the blast furnace. The basicity B2 of primary slag of the pellet, bosh slag, tuyere slag and final slag will then be 1.0, 1.1, 0.9 and 1.2, respectively.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…To decrease the variations in slag basicity and the slag amount in the cohesive zone, Ma 1) has proposed injection of fluxes through the tuyeres, instead of charging them from the top, to improve slag formation in the blast furnace. The basicity B2 of primary slag of the pellet, bosh slag, tuyere slag and final slag will then be 1.0, 1.1, 0.9 and 1.2, respectively.…”
Section: )mentioning
confidence: 99%
“…[1][2][3] At normal blast furnace operation, the tuyere slag, formed by the ash content in fuels combusted in front of the tuyeres, is very acidic and has a high viscosity. The injection of fluxes via the tuyeres makes it possible to increase the basicity of the tuyere slag to an appropriate level and improve its melting properties.…”
Section: )mentioning
confidence: 99%
“…Occasionally, reduction of gas/liquid permeability in the bosh zone during high PCR/low slag volume operations has been reported. [2][3][4] For high PCR/low slag volume operation, the gas/liquid permeability should be estimated with considering the slag chemistry, and it can be indirectly predicted by investigating the viscosity of bosh slags.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of the BOF-slag added is about 3% of the amount of pellet. Theoretical analyses conducted by Professor Ma 4) have shown that top-charged BOF-slag can improve slag formation when using olivine pellets, but does cause problems when using 100% self-fluxed pellets. For the latter, the top-charged BOF-slag with the primary slag phases from the pellets can form high-basicity bosh slag, especially when segregation of BOF-slag occurs.…”
Section: Introductionmentioning
confidence: 99%
“…One of the major reasons has been theoretically attributed to the worsening of the softening and melting properties of the pellet in the furnace, resulting from the top-charging of the fluxes together with pellets. 4) Conventionally, the major slag formers used at SSAB Luleå are BOF-slag and limestone, top-charged together with pellets. The amount of the BOF-slag added is about 3% of the amount of pellet.…”
Section: Introductionmentioning
confidence: 99%